Dialysis-related thrombocytopenia: a case report - Duayer,Irene Faria (2022)
Abstract Thrombocytopenia is frequently observed in hemodialysis patients, and its correct investigation and control remain a challenge. It is estimated that during the hemodialysis session there is a drop of up to 15% in the platelet count, with recovery after the end of treatment. This reduction in platelets is due to platelet adhesion and complement activation, regardless of the membrane material. Several studies with platelet surface markers demonstrate increased platelet activation and aggregation secondary to exposure to cardiopulmonary bypass. This case report describes a patient on hemodialysis who developed severe thrombocytopenia during hospitalization. Investigation and exclusion of the most common causes were carried out: heparin-related thrombocytopenia, adverse drug reaction, hypersplenism, and hematological diseases. Afterwards, the possibility of hemodialysis-related thrombocytopenia was raised, since the fall was accentuated during the sessions with partial recovery after the dialyzer change. Attention to the sterilization method and dialyzer reuse must be considered for correction. In the current case, reusing the dialyzer minimized the drop in platelet counts associated with hemodialysis.